Penerapan Prinsip Akad Mudharabah Pada Investasi Syariah Hewan Ternak PT Ijadgrup Rahmat Semesta - Mohammad Razan Mahrani; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2019)
This study aims to determine the application of sharia principles contained in the investment of livestock conducted by PT Ijadgrup Rahmat Semesta in his company called Ijadfarm. The approach used is qualitative approach with case study strategy. Data collection is done by interviewing with related parties. Analytical technique that is done is source triangulation technique, pattern matching technique and descriptive qualitative analysis technique. The results of this study are the sharia principles applied by Ijadfarm in the investment of livestock in accordance with sharia principles established by DSN MUI.Keywords: Principles of Sharia Investment, Mudharabah, Sharia Husbandry, Fatwa DSN MUI REFERENCESAffandi,L., Dikman, D.M dan Aryogi. 2007. Petunjuk Teknis Manajemen Perkawinan Sapi Potong. Pasuruan. Loka Penelitian Sapi PotongAntonio, Syafii. 2001. Bank Syariah dari Teori ke Praktik. Jakarta. Gema InsaniFatimah, Siti. 2011. Pelaksanaan Sistem Bagi Hasil Ternak Sapi di Desa Sejangat Ditinjau Menurut Konsep Mudharabah.Pekanbaru. Universitas Islam Negeri Sultan Syarif Kasim RiauHaming dan Basalamah. 2003. Studi Kelayakan Investasi: Proyek dan Bisnis. Jakarta. PPMHanoem, Halida. 2012. Keseuaian Implementasi Akad Mudharabah Musytarakah Pada Perusahaan Asuransi Takaful Keluarga Surabaya. Surabaya. Universitas Airlangga Haroen, Nasrun. 2007. Fiqh Muamalah. Jakarta. Gaya Media PertamaHenry Simamora. 2000. Basis Pengambilan Keputusan Bisnis. Salemba Empat. JakartaIskandar, L. 2009. Geografi 2 : Kelas XI SMA dan MA. Jakarta. PT Remaja RosdakaryaKarim Adiwarman. 2007. Bank Islam:Analisis Fiqh dan Keuangan. Jakarta. PT Raja Grafindo PersadaSalim dan Budi. 2008. Hukum Investasi di Indonesia. Jakarta. PT Raja Grafindo Persada Mansur. 2009. Seluk Beluk Ekonomi Islam.Salatiga. STAIN Salatiga PressMasadi, A.Ghufron. 2002. Fiqh Muamalah Kontekstual. Semarang. PT Raja Grafindo PersadaMuhammad. 2004. Teknik Bagi Hasil Keuntungan pada Bank Syariah.Yogyakarta. UII PressMuhammad. 2014. Manajemen Keuangan Syariah. Yogyakarta.UPP STIM YKPNMuslich, A.Wardi. 2010. Fiqh Muamalat. Jakarta. AmzahNafik, Muhammad. 2009. Bursa Efek dan Investasi Syariah. Jakarta. Serambi Ilmu SemestaSabiq, Sayyid. 1997. Fiqhus Sunnah jilid 3. Riyadh. Daarul MuayyadSugiyono. 2014. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung. CV Alfabeta. Sukirno, Sadono. 1997. Pengantar Teori Mikro Ekonomi Edisi 2. Jakarta. PT Raja Grafindo PersadaSunariyah, 2003.Pengantar Pengetahuan Pasar Modal Edisi 3. Yogyakarta.UPP-AMP YKPNSuwiknyo, D. 2009. Kompilasi Tafsir Ayat-Ayat Ekonomi Islam. Yogyakarta. Pustaka PelajarYin, K.Robert.2014.Studi Kasus “Desain & Metode”. Jakarta. PT Raja Grafindo PersadaOutlook Daging Sapi Kementrian Pertanian tahun 2016.